Association between Accessory Gene Regulator Polymorphism and Mortality among Critically Ill Patients Receiving Vancomycin for Nosocomial MRSA Bacteremia: A Cohort Study - Angélica Cechinel; Denise P. Machado; Eduardo Turra; Dariane Pereira; Rodrigo P. dos Santos; Regis G. Rosa; Luciano Z. Goldani (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Polymorphism of the accessory gene regulator group II (agr) in methicillin-resistant Staphylococcus aureus (MRSA) is predictive of vancomycin failure therapy. Nevertheless, the impact of group II agr expression on mortality of patients with severe MRSA infections is not well established. Objective. The goal of our study was to evaluate the association between agr polymorphism and all-cause in-hospital mortality among critically ill patients receiving vancomycin for nosocomial MRSA bacteremia. Methods. All patients with documented bacteremia by MRSA requiring treatment in the ICU between May 2009 and November 2011 were included in the study. Cox proportional hazards regression was performed to evaluate whether agr polymorphism was associated with all-cause in-hospital mortality. Covariates included age, APACHE II score, initial C-reactive protein plasma levels, initial serum creatinine levels, vancomycin minimum inhibitory concentration, vancomycin serum levels, and time to effective antibiotic administration. Results. The prevalence of group I and group II agr expression was 52.4% and 47.6%, respectively. Bacteremia by MRSA group III or group IV agr was not documented in our patients. The mean APACHE II of the study population was 24.3 (standard deviation 8.5). The overall cohort mortality was 66.6% (14 patients). After multivariate analysis, initial plasma C-reactive protein levels (P=0.01), initial serum creatinine levels (P=0.008), and expression of group II agr (P=0.006) were positively associated with all-cause in-hospital mortality. Patients with bacteremia by MRSA with group II agr expression had their risk of death increased by 12.6 times when compared with those with bacteremia by MRSA with group I agr expression. Conclusion. Group II agr polymorphism is associated with an increase in mortality in critically ill patients with bacteremia by MRSA treated with vancomycin.